Influence of white radish (Raphanus sativus L.) powder on the quality characteristics of set-type yogurt during cold storage - Isam A. Mohamed Ahmed; Fahad Y. Al Juhaimi; Hesham Al-Quh; Elfadil E. Babiker (CyTA - Journal of Food)
The quality attributes of a set-type yogurt fortified with different levels (0%, 2%, and 4%) of white radish powder (WRP) during cold storage were evaluated. WRP contains high total phenolic content (TPC, 276.8 mg GAE/100 g) and fiber (11.8%) and possessed high DPPH scavenging activity (63.35% inhibition). WRP increased the ash, fiber, TPC, DPPH scavenging activity, viscosity, acidity, water holding capacity (WHC), a*, b*, cohesiveness, springiness, and storage modulus (G´) and reduced the pH, total solids, syneresis, hardness, adhesiveness, protein, fat, L*, thiobarbituric acid (TBARS), gumminess, color, flavor, taste, smoothness, sourness, and general acceptability of yogurt. The pH, viscosity, WHC, hardness, gumminess, adhesiveness, TPC, DPPH scavenging activity, and sensory characteristics were reduced, whereas syneresis, acidity, a*, b*, G´, TBARS were augmented in all yogurt during storage with WRP-yogurt showed less changes indicating high storage stability of WRP-yogurt. Conclusively, WRP improved the quality attributes and storage stability of a set-type yogurt.